Approaches to appropriate care delivery from a policy perspective: A case study of Australia, England and Switzerland - Robertson-Preidler, J.; Anstey, Matthew; Biller-Andorno, N.; Norrish, A. (Elsevier Ireland Ltd, 2016)
Background: Appropriateness is a conceptual way for health systems to balance Triple Aim priorities for improving population health, containing per capita cost, and improving the patient experience of care. Comparing system approaches to appropriate care delivery can help health systems establish priorities and facilitate appropriate care practices. Methods: We conceptualized system appropriateness by identifying policies that aim to achieve the Triple Aim and their consequent trade-offs for financing, clinical practice, and the individual patient. We used secondary data sources to compare the appropriate care approaches of Australia, England, and Switzerland according to financial, clinical, and individual appropriateness policies. Findings: Health system approaches to appropriate care delivery varied. England prioritizes public health, equity and efficiency at the expense of individual choice, while Switzerland focuses on individual patient preferences, but has higher per capita and out of pocket costs. Australia provides equity in public care access and private health care options that allows for more patient choice, with health care costs falling between the two. Conclusions: Integrating the Triple Aim into health system design and policy can facilitate appropriate care delivery at the system, clinical, and individual levels. Approaches will vary and require countries to negotiate and justify priorities and trade-offs within the context of thehealth system.